Reactive Context-Aware Programming - Mostinckx, Stijn; Lombide Carreton, Andoni; De Meuter, Wolfgang (Electronic Communications of the EASST, 2008)
Using state of the art tools, context-aware applications are notified of relevant changes in their environment through event handlers which are triggered by dedicated middleware. The events signalled by the middleware should percolate through the entire application, requiring a carefully crafted network of observers combined with complex synchronization code to address the inherent concurrency issues. This paper proposes the adoption of reactive programming techniques to bridge the gap between the event-driven middleware and the application.